To Molecularly Block Hydrogen Evolution Sites of Molybdenum Disulfide toward Improved Catalytic Performance for Electrochemical Nitrogen Reduction. Issue 3 (6th January 2023) - Win, Poe Ei Phyu; Yu, Dongxue; Song, Wenjuan; Huang, Xiang; Zhu, Peng; Liu, Guanyu; Wang, Jiong
Abstract: 2H‐molybdenum disulfide (2H‐MoS2 ) represents a classical catalyst for the electrochemical N2 reduction reaction (NRR) in water that offers a promising technology toward sustainable production of NH3 driven by renewable energy. While the catalytic efficiency is severely limited by a simultaneous and competing H2 evolution reaction (HER). Herein, it is proposed that the S edge of 2H‐MoS2, which is known as main sites to afford HER, is intentionally covered by cobalt phthalocyanine (CoPc) molecules through axial coordination. While the Mo sites with S vacancies at 2H‐MoS2 edge is recognized as highly NRR active, and can keep structurally intact in the CoPc based modification. The resultant composite thus exhibits high NRR performance with Faradic efficiency and NH3 yields increase by fourfold and twofold, respectively, comparing to pristine 2H‐MoS2 . These findings provide a deep insight into the mechanism of 2H‐MoS2 based NRR catalysis and suggest an efficient molecular modification strategy to promote NRR in water. Abstract : 2H‐molybdenum disulfide (2H‐MoS2 ) is extensively applied for electrochemical nitrogen reduction, but the catalytic efficiency is limited by the competing hydrogen evolution. This work shows that the hydrogen evolution sites of 2H‐MoS2 can be molecularly blocked by cobalt phthalocyanine through potential axial coordination. The strategy is efficient to improve the nitrogen reduction activity of 2H‐MoS2 .